PERAN ETIKA KONSELOR DALAM PELAKSANAAN BIMBINGAN DAN KONSELING DI SEKOLAH - Alda Mafrika Fauziyah; Yusnita Hikmawati; Rahmi Anekasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The professional ethics of counselors play a key role in the implementation of guidance and counseling in schools, serving as a source of trust, protection, and well-being for professional services. This study examines the role of professional ethics and the principles of professional ethics as outlined in the Indonesian Code of Ethics for Counselors (KEKI). Through a qualitative descriptive approach, literature review, and document analysis of 10-15 counselors in several schools, the findings indicate that professional ethics builds trust, maintains authority, and prevents abuse of authority, while respecting religious, cultural, and human rights values. However, this discussion uncovered challenges such as a lack of understanding of professional ethics, inadequate training, and tasks that hinder counselors from maintaining integrity, competence, and professional relationships. The findings of this study demonstrate that professional ethics is not merely a formal rule but also serves as a moral foundation that determines the quality of guidance and counseling in schools, making it suitable and relevant for developing ethics-based guidance and counseling policies in schools that support student character development. Keywords: professional ethics, guidance and counseling, professional integrity